SCHOOL ANXIETY IN ADOLESCENTS-PERFECTIONISTS: CORRECTION EXPERIENCE - Vavilova, Alyona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the study of school anxiety in adolescents-perfectionists and exploring ways of its correction. It was found that high levels of perfectionism in adolescents can increase the probability of impaired emotional well-being and, in particular, excessive levels of anxiety. To determine the level of perfectionism and components of school anxiety in pupils, two psychodiagnostic methods were used: the “Child-Adolescent Perfectionism Scale” by P. Hewitt and G. Flett and the “Multidimensional Anxiety Scale” by K. Malkova. The study of school anxiety was conducted in two stages: before and after correction. The correction involved setting realistic goals and adequate requirements for oneself; formation the ability for justified risk; shifting focus on achievement, not failure. The results of a comparative analysis of anxiety before and after correction in the participants of the experimental group indicated a statistically significant decrease anxiety related to the assessment of others; anxiety in relationships with teachers; anxiety related to school success; anxiety in knowledge testing situations. The results of a comparative analysis of experimental and control groups adolescents-perfectionists confirmed the effectiveness of corrective action aimed at reducing school anxiety due to the presence of destructive perfectionist attitudes.